Colony size and initial conditions combine to shape colony reunification dynamics - Doering, Grant Navid; Sheehy, Kirsten A.; Barnett, James B.; Pruitt, Jonathan N. (Behavioural processes, 2020)
•Ant colonies often live in a single nest but can also split between several nests concurrently.•We investigated what group traits and initial conditions promote or deter the reunification of multi-nest colonies.•Larger colonies and a lack of a central information hub both diminished the likelihood of colony reunification.•Colonies were no worse at reunifying when split between additional nests. Group cohesion and collective decision-making are important for many social animals, like social insects, whose societies depend on the coordinated action of individuals to complete collective tasks. A useful model for understanding collective, consensus-driven decision-making is the fluid nest selection dynamics of ant colonies. Certain ant species oscillate between occupying multiple nests simultaneously (polydomy) and reuniting at a single location (monodomy), but little is known about how colonies achieve a consensus around these dynamics. To investigate the factors underpinning the splitting-reunification dynamics of ants, we manipulated the availability and quality of nest sites for the ant Temnothorax rugatulus and measured the likelihood and speed of reunification from contrasting starting conditions. We found that pursuing reunification was more likely for smaller colonies, that rates of initial splitting were lower when colonies could coordinate their activity from a central hub, and that diluting colonies among additional sites did not impair reaching consensus on a single nest. We further found mixed support for a specific threshold of social density that prevents reunification (i.e., prolonged polydomy) and no evidence that nest quality influences reunification behavior. Together our data reveal that consensus driven decisions can be influenced by both external and intrinsic group-level factors and are in no way simple stereotyped processes.